2018
DOI: 10.1021/acs.langmuir.8b02677
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Insights into the Interactions between Star-Shaped Antimicrobial Polypeptides and Bacterial Membranes

Abstract: A structurally nanoengineered antimicrobial polypeptide consisting of lysine and valine residues is a new class of antimicrobial agent with superior antibacterial activity against multidrug-resistant bacteria and low toxicity toward mammalian cells. Utilizing coarse-grained models, we studied the interactions of microbial cytoplasmic membranes with polypeptides of either (K 2 V 1 ) 5 (star-KV) or CM15 (star-CM15). Our computational results verify the low toxicity of polypeptides of (K 2 V 1 ) 5 toward the dipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…In addition, the antibacterial mechanism of antibacterial peptides differs from those of existing antibiotics. Studies have shown that antimicrobial peptides prevent bacterial metabolism by reorganizing the liposome domain distribution, thus causing bacterial death [4]. Antibacterial peptides destroy bacteria by physically disrupting the structure of their cell membranes, making it difficult for bacteria to easily become resistant [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the antibacterial mechanism of antibacterial peptides differs from those of existing antibiotics. Studies have shown that antimicrobial peptides prevent bacterial metabolism by reorganizing the liposome domain distribution, thus causing bacterial death [4]. Antibacterial peptides destroy bacteria by physically disrupting the structure of their cell membranes, making it difficult for bacteria to easily become resistant [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The low toxicity was possibly due to SNAPPs' weak hydrophobicity together with random coil structure in the lysine/valine arm when interacting with mammalian cells. 72 Although the antimicrobial activity of SNAPPs was better than classic AMPs, their potency diminished in the presence of divalent cations and serum protein. 73 Arm number and length in star-polymer SNAPPs had a signicant inuence on their antimicrobial activity.…”
Section: Star Cationic Polymermentioning
confidence: 99%
“…11–16 A large quantity of synthetic AMPs with novel bactericidal activity and high selectivity have been reported. 6,17–19 Recently, some studies have addressed that the topology of AMPs has a profound influence on their activity, 20–33 especially, Qiao et al 23 recommended that the star-shaped AMPs denoted significantly higher antibacterial activities than their linear analogues. The elevated local cationic charge concentration of star-shaped AMPs that result in a greater cell membrane-induced polypeptide aggregation and a stronger electrostatic interaction between the AMPs and the bacterial membranes may be the main reason for the lower threshold concentration for membrane disruption.…”
Section: Introductionmentioning
confidence: 99%